Morphological differences of crickets in different generations: A case study on the Sonotrella (s. str.) laosensis Liu, Zhang & Shi, 2016 (Orthoptera: Grylloidea: Oecanthidae) - Ma, Yong; Liu, Yuwei; Liu, Haoyu (Zootaxa, 2025)
While some cricket species can undergo two or more generations per year, limited research has been conducted on the stability of external morphological characteristics across different generations. This study provides a comparative morphological analysis of using materials collected from Sonotrella (s. str.) laosensis in Laos during both the rainy and dry seasons. For the first time, it reveals variations in the stability of phallus among different generations. These research findings will provide valuable evidence to support the establishment of new units within cricket taxonomy, particularly when discussing subspecies status.